On the Meaning and Impact of the Physician-Assisted Suicide Cases. (Symposium: Physician-Assisted Suicide: Facing Death After Glucksberg and Quill) - Kamisar, Yale (1998)
I read every newspaper article I could find on the meaning and impact of the U.S. Supreme Court's June 1997 decisions in Washington v. Glucksberg' and Vacco v. Quill.2 I came away with the impression that some proponents of physician-assisted suicide (PAS) were unable or unwilling publicly to recognize the magnitude of the setback they suffered when the Court handed down its rulings in the PAS cases